A new dynamic bolt design with improved resin mixing and high-capacity anchoring - Evans, D.W.; Witter, P. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Dynamic rockbolts continue as an important geotechnical requirement for deep and high-stress mining environments, with product development work progressively evolving within this technical arena. For rockbolts used as primary ground support, numerous approaches have been taken to design ground support elements that provide initial stiff anchoring and load-bearing response for static ground conditions, but further to this, are able to perform dynamically in a rockburst event where rapid load onset and associated rock mass displacements can occur within the order of milliseconds. The fundamental requirements of a rockbolt design are to deliver secure anchoring within the rock mass, the transfer of load from the rock mass to the bolting element and to deliver the required mechanical response of the bolt element as it remains anchored within the displacing rock mass, ideally for both static and dynamic conditions. Geotechnical performance, simplicity in design and ease of installation remain primary considerations, these requirements being true of any ground support element. Polyester resin cartridges that employ a two-component resin and catalyst format are commonly used to provide bonding and encapsulation for rockbolts installed within pre-drilled boreholes, typically providing excellent load transfer properties for the installed system. However, during rotational installation of the rockbolt, if the two components are not well mixed within the borehole, resin curing, strength and load transfer are ultimately compromised. This paper outlines the development and validation of a new dynamic rockbolt design that addresses the fundamental requirement for well-mixed and cured cartridge resin, providing reliable anchoring and load transfer that exceeds the capacity of the bar element. Centric to this bolt design is a simplified and robust dynamic mechanism that provides repeatable performance and achieves the full mechanical energy available from the bar element during rock mass displacement. For industry reference, this new dynamic bolt design is the Sandvik ‘Versamix’ bolt.